MiR‐375‐3p/YWHAZ/β‐catenin axis regulates migration, invasion, EMT in gastric cancer cells. (21st December 2018) - Guo, Feng; Gao, Yongjian; Sui, Guoqing; Jiao, Dan; Sun, Lina; Fu, Qingfeng; Jin, Chunxiang
Summary: YWHAZ (14‐3‐3ζ) plays crucial roles in regulating proliferation, apoptosis, migration, and invasion of gastric cancer (GC) cells. However, its extensive roles and potential mechanisms in GC cells remain unknown, and need to be researched deeply. In this study, we focus on the role of miR‐375/YWHAZ axis in migration, invasion and epithelial‐to‐mesenchymal transition (EMT) of GC cells. YWHAZ level was assessed by western blot and qPCR assays in GC cells. Scratch and transwell assays were used to determine the migration and invasion of GC cells. The protein levels of correlative molecules were detected by western blot. The regulation of miR‐375 on the expression of its target gene YWHAZ was verified by dual‐luciferase report system. According to the results, knockdown of YWHAZ inhibited the migration, invasion and EMT of GC cells. Moreover, silencing of YWHAZ restrained the activation of wnt/β‐catenin signalling pathway. YWHAZ was confirmed to be a target gene of miR‐375, and its expression was regulated by miR‐375 in GC cells. Transfection of miR‐375 inhibitor promoted the migration, invasion, EMT and activation of wnt/β‐catenin pathway in GC cells, which was suppressed by inhibition of YWHAZ. Taken together, this study suggests that miR‐375/YWHAZ axis may be served as a novel therapeutic target for GC patients.